Synthesis and properties evaluation of sodium grease formulated from used transformer oil as base oil - N. S. A., Japar; Mohd Aizudin, Abd Aziz; Hamid, N. (IOP Publishing, 2020)
This study aimed to prepare sodium grease using used transformer oil as a base oil and investigate the prepared grease properties. Oil, whether it is new or used, is a significant contributor to water pollution due to its toxicity towards the environment. In this study, used transformer oil (UTO) is utilized as grease’s base oil. The properties of the grease were evaluated in terms of their consistency, drop point, oil separation, and bled oil in accordance with ASTM D217, D2265, D1742, and IP 121, respectively. The grease also characterized by using the FTIRATR. The results show that the grease can be formulated using UTO with significant grease properties of >180 °C dropping point, −15% to +15% of oil bleeding at both 25 °C and 70 °C, no separated oil during storage, and slightly tarnish on copper strip. The best UTO-based sodium grease formulation was 67.5:32.5 of oil-to-thickener ratio and it was classified as NLGI 2 grease. Moreover, the FTIR spectrum shows no contaminants or unknown chemical changes or additive in UTO and the prepared grease. The addition of MoS2 in grease shows no significant improvement in sodium grease properties. Thus, UTO was able to work as grease base oil and exhibited overall good properties but, UTO-based grease analysis on its tribology is necessary to study the prepared grease performances during operation.